The impact of sound in people's behaviour in outdoor settings: A study using virtual reality and eye-tracking - Eloy, S.; Andrade, M. A. P.; Dias, L.; Dias, J. (Applied Ergonomics, 2023)
This paper presents an analysis of space perception and how visual cues, such as landmarks and sound, are perceived and impact people's behaviour while exploring a given outdoor space. The primary goal of the research is to investigate how auditory sensations and visual stimuli influence people's behaviour in outdoor built environments. Our technique compares people's perception of the built environment in different conditions: the real world and a replicated virtual world. As a case study, a university campus was used, and four experimental conditions were designed. The study followed a between-subjects design, and the data collection included gaze data acquired from an eye-tracking device as well as self-reports. The study concludes that sound influences human behaviour in such settings. More specifically conclusions are that: i) human behaviour in virtual replications of the real space, including both visual and sound stimuli, is tendentially more similar to human behaviour in the real world than in simulations omitting sound; and ii) there is a difference in human behaviour when people explore the same virtually replicated outdoor space, by varying the presence of sound. This study is particularly useful for researchers working on the comparison between human behaviour in virtual and real environments, related to visual and sound stimuli.